Modulatory and regenerative potential of transplanted bone marrow derived mesenchymal stem cells on rifampicin-induced kidney toxicity - Danjuma, Lawal; Pooi, Ling Mok; Higuchi, Akon; Awang Hamat, Rukman; Seoh, Wei Teh; Avin Ee, Hwan Koh; A.Munusamy, Murugan; Arulselvan, Palanisamy; Rajan, Mariappan; Nambi, Arivudai; Swamy, K. B.; Vijayaraman, Kiruthiga; et al. (Elsevier, 2018)
Anti-tuberculosis agent rifampicin is extensively used for its effectiveness. Possible complications of tuberculosis and prolonged rifampicin treatment include kidney damage; these conditions can lead to reduced efficiency of the affected kidney and consequently to other diseases. Bone marrow-derived mesenchymal stem cells (BMMSCs) can be used in conjunction with rifampicin to avert kidney damage; because of its regenerative and differentiating potentials into kidney cells. This research was designed to assess the modulatory and regenerative potentials of MSCs in averting kidney damage due to rifampicin-induced kidney toxicity in Wistar rats and their progenies. BMMSCs used in this research were characterized according to the guidelines of International Society for Cellular Therapy.